Effect of Luteolin and Apigenin on the Expression of Oct-4, Sox2, and c-Myc in Dental Pulp Cells with In Vitro Culture. (26th February 2015) - Liu, Lu; Peng, Zhengjun; Xu, Zezhen; Wei, Xi
Abstract : Introduction . Dental pulp cells (DPCs) are promising cell source for dental tissue regeneration. Recently, small molecules which optimize microenvironment or activate the reprogramming network provide a new way to enhance the pluripotency. Two promising bioflavonoids luteolin and apigenin were reported to enhance reprogramming efficiency in mouse embryonic fibroblast (MEF). However, their effect and underlying mechanism in cell fate determination of human DPCs remain unclear. Methods . To elucidate the effect of luteolin and apigenin on the cell fate determination of DPCs, we explored the cell proliferation, cell cycle, senescence, apoptosis, expression of pluripotency markers Oct-4, Sox2, and c-Myc, and multilineage differentiation capability of DPCs with luteolin or apigenin treatment. Results . We demonstrated that luteolin and apigenin inhibited cell proliferation, arrested DPCs in G2/M and S phase, and upregulated PI value and apoptosis. Moreover, luteolin and apigenin increased telomerase activity, maintained DPCs in a presenescent state, and activated the expression of Oct-4, Sox2, and c-Myc at a dose- and time-dependent pattern in DPCs even at late passages, albeit repressed lineage-specific differentiation. Conclusions . Addition of luteolin and apigenin in the culture medium might provide an effective way to maintain DPCs in an undifferentiated stage and inhibit lineage-specific differentiation.